A high-strength and high-toughness silane-modified sealant and preparation method thereof
By using aluminate surface treatment agent and reinforcement toughening agent in silane modified sealant, the problem of insufficient flexibility and compatibility of silane modified sealant is solved, and its strength and bonding properties are significantly improved. High performance sealing applications in industrial fields.
Patent Information
- Application Number
- CN202211698664.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-28
AI Technical Summary
Silane modified sealants have shortcomings in both high strength and high toughness, especially poor flexibility and poor compatibility, which leads to certain limitations in industrial applications.
Using aluminate surface treatment agent with silicon oxygen segments and reinforcing toughening agent for reactive groups, the inorganic powder is modified to improve the filling amount and compatibility of the inorganic filler, and participate in the hydrolysis reaction to improve sealing. Plasticity and adhesive properties of glue.
It significantly improves the strength, toughness and adhesive properties of the sealant, reduces the water absorption rate and oil absorption, improves the interface compatibility between the inorganic powder and the organic resin, and enhances the mechanical properties of the material.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silane-modified adhesives, and in particular relates to a high-strength and high-toughness silane-modified sealant and a preparation method thereof. Background Art
[0002] Silane modified sealant is a high-performance environmentally friendly sealant made from a polymer based on terminal silane polyether / polyurethane (polyether / polyurethane as the main chain, with siloxane end capping at both ends). Because it has the advantages of both silicone sealant and polyurethane sealant, it exhibits excellent weather resistance, durability, high resistance to deformation and displacement, good adhesion, coating, environmental friendliness, low stain resistance, low viscosity and excellent workability. It has been increasingly concerned by the domestic construction industry, and is also being widely promoted and applied in industrial fields such as automobile manufacturing, rail transportation, container manufacturing, equipment manufacturing, and electronic and electrical fields.
[0003] Silane-modified sealants have the advantages of both silicone sealants and polyurethane sealants, but also have the moisture sensitivity and poor compatibility of polyurethane sealants, which places higher requirements on the moisture content of reinforcing fillers and surface treatment.
[0004] Due to the structural regularity of the polyether chain segments, the molecular segments are arranged relatively closely, and the polyurethane segment (urethane group) structure has strong intermolecular forces, which makes the hardness and modulus of silane-modified sealants higher than those of silicone sealants, and the flexibility is also poorer than that of silicone. This problem is usually solved by adding plasticizers to silane-modified sealants. The increase of plasticizers will also bring about problems such as precipitation. At the same time, although the strength of silane-modified sealants with polyether / polyurethane as the main chain is higher than that of silicone sealants, it is significantly lower than that of polyurethane sealants. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a high-strength and high-toughness silane-modified sealant and a preparation method thereof.
[0006] The specific technical solutions of the present invention are as follows:
[0007] The first object of the present invention is to provide a high-strength and high-toughness silane-modified sealant, comprising the following components in parts by weight:
[0008] Silane modified resin 10-40 parts; nano calcium carbonate 30-70 parts; surface modifier 0.1-2 parts; plasticizer 1-20 parts; UV aging agent 0.1-2 parts; antioxidant 0.1-2 parts; reinforcing and toughening agent 0.5-10 parts; dewatering agent 1-10 parts; coupling agent 1-15 parts; catalyst 0.01-5 parts;
[0009] The surface treatment agent is an aluminate treatment agent.
[0010] Furthermore, the structural formula of the surface treatment agent is as shown in formula (1):
[0011]
[0012] Where n≤3, m=7 or 8.
[0013] Furthermore, the synthesis method of the surface treatment agent is as follows:
[0014] In a reactor, diisopropoxy acetoacetic acid oleate aluminate is dissolved in a toluene solution, the temperature is raised to 60°C, single-terminal hydrogen-containing silane is added in a molar ratio of 1:1, and the reaction is carried out for 2 hours under the action of a platinum catalyst. The product is placed in a vacuum drying oven and dried at 60°C for 24 hours to obtain a white or yellow aluminate containing silicon-oxygen segments. The reaction equation is as follows:
[0015]
[0016] Where n≤3, m=7 or 8.
[0017] The above further technical features have the following technical effects:
[0018] Compared with other coupling agents, such as titanate, borate, etc., inorganic powders activated and modified by aluminate coupling agents have the advantages of light color, non-toxicity, small odor, easy use, low price, etc. in addition to stable quality. Because the surface undergoes chemical or physical action to generate an organic molecular layer, the hydrophilicity becomes organic affinity, which enhances the interfacial compatibility between the inorganic powder and the organic resin. Therefore, the surface treatment agent modified by aluminate coupling agent can not only improve the processing performance of plastic products filled with inorganic powder, but also significantly improve the physical and mechanical properties of the products, reduce the water absorption rate of the product, reduce the oil absorption, and evenly disperse the filler. The present invention utilizes addition reaction to introduce siloxane segments into aluminate, and further improves the compatibility of inorganic powder with silane modified resin on the above basis, increases the filling amount of inorganic filler, and retains the good mechanical properties of the material.
[0019] Furthermore, the structural formula of the reinforcing and toughening agent is as shown in formula (2):
[0020]
[0021] Where x≤3.
[0022] The above further technical features have the following technical effects:
[0023] The introduction of the silane chain segment of the reinforcing and toughening agent of the present invention increases flexibility and toughness, and is also beneficial to improving compatibility and improving the strength of the sealant; the introduction of the phenyl and epoxy chain segments improves the bonding performance of the sealant with various substrates; the presence of the silane alkoxy chain segment can participate in the hydrolysis reaction, improve the plasticity of the sealant before the reaction, and after participating in the reaction, the silane-modified epoxy resin will not undergo free migration like ordinary plasticizers, and at the same time participate in chain extension to improve elongation and increase the flexibility of the sealant.
[0024] Furthermore, the silane-modified resin is one or two or more polyether / polyurethane terminated with silane groups; wherein the silane groups are dialkoxysilane groups and / or trialkoxysilane groups, preferably commercially available S203H, S303H, S810, S943 of Zhongyuan; STP-E15, E35 of Wacker; S416, S618 of Shanghai Dongda Chemical, etc.
[0025] Furthermore, the nano calcium carbonate is commercially available domestic calcium carbonate, such as one or two or more of Guangxi Warner 25, Shanxi Lanhua SP200, and Hubei Kailong S034.
[0026] Furthermore, the plasticizer is one of polyether polyol and diisononyl phthalate (DINP); the anti-ultraviolet aging agent is one or both of UV329 and light stabilizer 770; and the antioxidant is one of 1010 and 1076.
[0027] Furthermore, the dehydrating agent is vinyltrimethoxysilane (A-171); the coupling agent is one or two or more of KH550, KH560, KH570, and KH792; and the catalyst is a chelated tin catalyst, preferably U-220H.
[0028] The second object of the present invention is to provide a method for preparing a high-strength and high-toughness silane-modified sealant, comprising the following steps:
[0029] In a reaction kettle, add the silane modified resin, nano calcium carbonate, and surface modifier, mix well, heat to 60-80°C for reaction for 1-2h, then heat to 110-120°C for reaction for 1-2h, then add plasticizer, UV aging agent, and antioxidant and mix well, stir for 1-2h at a vacuum of -0.1 to -0.06MPa and a temperature of 110-120°C, then cool to below 50°C, add reinforcing plasticizer, dehydrating agent, coupling agent, and catalyst, mix well in vacuum, release pressure with nitrogen, and seal the discharged material for storage.
[0030] The beneficial effects of the present invention are:
[0031] The invention uses a self-made aluminate surface treatment agent containing silicon oxygen segments to improve the compatibility of inorganic powders and silane modified resins, increase the filling amount of inorganic fillers, and retain good mechanical properties of the material. At the same time, a reinforcing and toughening agent containing reactive groups is added to improve the plasticity of the sealant before the reaction, and after the reaction, free migration will not occur, thereby improving the strength and flexibility of the sealant, increasing the elongation, and improving the bonding performance with various substrates. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] The structural formula of the self-made surface treatment agent used in the examples or comparative examples of the present invention is shown in formula (1):
[0034]
[0035] Where n≤3, m=7 or 8.
[0036] The synthesis method of the above-mentioned surface treatment agent is as follows:
[0037] In a flask, diisopropoxy acetoacetic acid oleate aluminate is dissolved in a toluene solution, the temperature is raised to 60°C, single-terminal hydrogen-containing silane is added in a molar ratio of 1:1, and the reaction is carried out under the action of a platinum catalyst for 2 hours. The product is dried in a vacuum drying oven at 60°C for 24 hours to obtain a white or yellow aluminate containing silicon-oxygen segments. The reaction equation is as follows:
[0038]
[0039] Where n≤3, m=7 or 8.
[0040] The reinforcing and toughening agent used in the embodiments or comparative examples of the present invention has a structural formula as shown in formula (2):
[0041] Furthermore, the structural formula of the reinforcing and toughening agent is as shown in formula (2):
[0042]
[0043] Where x≤3.
[0044] Embodiment 1:
[0045] A method for preparing a silane-modified sealant is as follows:
[0046] In a reaction kettle, 30 parts by weight of silane-modified polyether resin S303H, 50 parts of nano calcium carbonate KLMN-034 and 0.5 parts of a self-made surface modifier of structural formula (1) where n=2 were added, mixed evenly, heated to 70°C and stirred for 1.5h, then heated to 115°C and stirred for 1.5h, then 5 parts of plasticizer DINP, 0.3 parts of UV-resistant aging agent UV-329, 0. After 3 parts of antioxidant 1010 are mixed, vacuum -0.09MPa, stir at 115°C for 1.5h, cool to below 50°C with cooling water, add 4 parts of reinforcing plasticizer as shown in structural formula (2) where x=2, 1.5 parts of dehydrating agent A-171, 1 part of coupling agent KH570, 2 parts of coupling agent KH792, 0.5 parts of catalyst U-220H, vacuum mix evenly, release the pressure with nitrogen, and seal the discharged material for storage.
[0047] Embodiment 2:
[0048] A method for preparing a silane-modified sealant is as follows:
[0049] In a reaction kettle, 30 parts by weight of silane-modified polyether resin S303H, 55 parts of nano-calcium carbonate KLMN-034 and 1 part of a homemade surface modifier of structural formula (1) wherein n=2 are added, and after mixing evenly, the mixture is heated to 70° C. and stirred for 1.5 h, and then stirred at 115° C. for 1.5 h. Then, 5 parts of plasticizer DINP, 0.3 parts of UV-resistant aging agent UV-329 and 0.3 parts of antioxidant 1010 are added and mixed evenly. The mixture is stirred at -0.09 MPa in vacuum at 115° C. for 1.5 h, and then cooled to below 50° C. by cooling water. Then, 4 parts of a reinforcing plasticizer of structural formula (2) wherein x=2, 1.5 parts of a dehydrating agent A-171, 1 part of a coupling agent KH570, 2 parts of a coupling agent KH792 and 0.5 parts of a catalyst U-220H are added, the mixture is mixed evenly in vacuum, the pressure is released by nitrogen and the discharged material is sealed and stored.
[0050] Embodiment 3:
[0051] A method for preparing a silane-modified sealant is as follows:
[0052] In a reaction kettle, 30 parts by weight of silane-modified polyether resin S303H, 50 parts of nano-calcium carbonate KLMN-034 and 0.5 parts of a homemade surface modifier such as structural formula (1) wherein n=2 are added, mixed evenly, heated to 70°C and stirred for 1.5 hours, then heated to 115°C and stirred for 1.5 hours, then 5 parts of plasticizer DINP, 0.3 parts of UV-resistant aging agent UV-329 and 0.3 parts of antioxidant 1010 are added and mixed evenly, vacuum-treated at -0.09 MPa and 115°C, stirred for 1.5 hours, cooled to below 50°C by cooling water, and 8 parts of a reinforcing plasticizer such as structural formula (2) wherein x=2, 1.5 parts of a dehydrating agent A-171, 1 part of a coupling agent KH570, 2 parts of KH792 and 0.5 parts of a catalyst U-220H are added, mixed evenly in vacuum, depressurized with nitrogen and the discharged material is sealed and stored.
[0053] Embodiment 4:
[0054] A method for preparing a silane-modified sealant is as follows:
[0055] In a reaction kettle, 30 parts by weight of silane-modified resin S426 containing carbamate segments, 50 parts of nano-calcium carbonate KLMN-034 and 0.5 parts of a homemade surface modifier such as structural formula (1) wherein n=2 are added, mixed evenly, heated to 70° C. and stirred for 1.5 h, then stirred at 115° C. for 1.5 h, then 5 parts of plasticizer DINP, 0.3 parts of UV-resistant aging agent UV-329 and 0.3 parts of antioxidant 1010 are added and mixed evenly, vacuum-treated at -0.09 MPa and 115° C., stirred for 1.5 h, cooled to below 50° C. with cooling water, then 4 parts of reinforcing plasticizer such as structural formula (2) wherein x=2, 1.5 parts of dehydrating agent A-171, 1 part of coupling agent KH570, 2 parts of KH792 and 0.5 parts of catalyst U-220H are added, mixed evenly in vacuum, depressurized with nitrogen and the discharged material is sealed for storage.
[0056] Embodiment 5:
[0057] A method for preparing a silane-modified sealant is as follows:
[0058] In a reaction kettle, 30 parts by weight of silane-modified resin S426 containing carbamate segments, 50 parts of nano-calcium carbonate KLMN-034 and 1 part of a homemade surface modifier of structural formula (1) wherein n=2 are added, mixed evenly, heated to 70° C. and stirred for 1.5 h, then stirred at 115° C. for 1.5 h, then 5 parts of plasticizer DINP, 0.3 parts of UV-resistant aging agent UV-329 and 0.3 parts of antioxidant 1010 are added and mixed evenly, stirred at -0.09 MPa and 115° C. for 1.5 h, cooled to below 50° C. by cooling water, then 8 parts of reinforcing plasticizer of structural formula (2) wherein x=2, 1.5 parts of dehydrating agent A-171, 1 part of coupling agent KH570, 2 parts of KH792 and 0.5 parts of catalyst U-220H are added, mixed evenly in vacuum, depressurized with nitrogen and the discharged material is sealed for storage.
[0059] Comparative Example 1
[0060] The difference from Example 1 is that no surface modifier and reinforcing and toughening agent are added.
[0061] Comparative Example 2
[0062] The difference from Example 1 is that no surface modifier is added.
[0063] Comparative Example 3
[0064] The difference from Example 1 is that no reinforcing and toughening agent is added, and the amount of plasticizer is changed to 9 parts.
[0065] Comparative Example 4
[0066] The difference from Example 4 is that no surface modifier is added.
[0067] Comparative Example 5
[0068] The difference from Example 4 is that no reinforcing and toughening agent is added, and the amount of plasticizer is changed to 9 parts.
[0069] Test Examples
[0070] The performance of the above-mentioned Examples 1-5 and Comparative Examples 1-5 of the present invention were tested by the following experiments.
[0071] Sealant curing conditions: 25°C, 50% RH, 7 days.
[0072] The relevant tests are as follows:
[0073] Test 1 Extrusion rate test
[0074] Test conditions: 30cc hose, pore diameter 2.4mm, pressure 0.6MPa.
[0075] Test method: weigh the amount of glue discharged per minute, unit: g / min.
[0076] Test 2 Tensile test
[0077] The tensile strength and elongation at break are tested using an electronic tensile testing machine in accordance with GB / T528-2008, a test standard for tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.
[0078] Test 3: Adhesion test
[0079] The sealant was degassed and applied to the aluminum plate and PC plate respectively. After AL-AL and PC-PC were overlapped, they were cured according to the above curing conditions and tested according to the determination standard of tensile shear strength of adhesives GB / T7124-2008.
[0080] The test results of Examples 1-5 are shown in Table 1, and the test results of Comparative Examples 1-5 are shown in Table 2.
[0081] Table 1 Performance test results of samples obtained in Examples 1-5
[0082] Example 1 Example 2 Example 3 Example 4 Example 5 Extrusion rate (g / min) 260 200 300 200 240 Tensile strength(MPa) 2.8 3.5 3.5 4.0 4.2 Elongation at break, % 300 300 320 200 280 PC bonding strength (MPa) 4.0 4.2 4.5 8.6 10 AL bonding strength (MPa) 3.0 3.2 3.5 4.0 5.2
[0083] Table 2 Performance test results of samples obtained from comparative examples 1-5
[0084] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Extrusion rate (g / min) 120 180 280 130 210 Tensile strength(MPa) 2.0 2.6 2.0 3.7 3.5 Elongation at break, % 150 280 240 160 120 PC bonding strength (MPa) 2.5 3.8 2.8 7.5 6.5 AL bonding strength (MPa) 1.8 2.8 2.0 3.6 3.2
[0085] From the performance test results in Table 1 and Table 2, it can be seen that the extrusion rate of Example 1 is significantly higher than that of Comparative Example 2, and the extrusion rate of Example 4 is also significantly higher than that of Comparative Example 4. It can be seen that the homemade surface modifier can effectively treat the surface of the inorganic filler and reduce the viscosity of the sealant.
[0086] Compared with Comparative Examples 1 and 3, the extrusion rate of Example 1 is significantly higher than that of Comparative Example 1 and is close to that of Comparative Example 3. Meanwhile, the extrusion rate of Example 4 is also close to that of Comparative Example 5. The addition of the reinforcing plasticizer described in the present invention can effectively reduce the viscosity of the sealant and improve the plasticity of the sealant before reaction.
[0087] Compared with Comparative Examples 2 and 3, and compared with Comparative Example 5, Examples 4 and 5 have significantly improved tensile strength, elongation and adhesion to different materials, indicating that the reinforcing and toughening agent has improved the strength and toughness of the sealant to varying degrees; compared with Example 3, it can be seen that the reinforcing and toughening agent of the present invention has significantly improved the strength of the polyether type silane modified sealant; compared with Examples 4 and 5, and Examples 4 and 5 have been compared with Comparative Example 5, it can be seen that the reinforcing and toughening agent has significantly improved the elongation of the polyurethane type modified silane sealant, that is, the toughening effect is more obvious.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength and high-toughness silane-modified sealant, characterized in that: The composition comprises the following components in parts by weight: Silane modified resin 10-40 parts; nano calcium carbonate 30-70 parts; surface treatment agent 0.1-2 parts; plasticizer 1-20 parts; 0.1-2 parts of UV aging agent; 0.1-2 parts of antioxidant; 0.5-10 parts of reinforcing and toughening agent; 1-10 parts of dehydrating agent; 1-15 parts of coupling agent; 0.01-5 parts of catalyst; The silane-modified resin is one or more of a polyether terminated with a silane group or a polyurethane terminated with a silane group; wherein the silane group is a dialkoxysilane group and / or a trialkoxysilane group; The structural formula of the surface treatment agent is shown in formula (1): Formula (1) Where n≤3, m=7 or 8; The structural formula of the reinforcing and toughening agent is shown in formula (2): Formula (2) Where x≤3.
2. The high-strength and high-toughness silane-modified sealant according to claim 1, characterized in that: The synthesis method of the surface treatment agent is as follows: In a reactor, diisopropoxy acetoacetic acid oleate aluminate is dissolved in a toluene solution, the temperature is raised to 60°C, single-terminal hydrogen-containing silane is added in a molar ratio of 1:1, and the reaction is carried out for 2 hours under the action of a platinum catalyst. The product is placed in a vacuum drying oven and dried at 60°C for 24 hours to obtain a white or yellow aluminate containing silicon-oxygen segments. The reaction equation is as follows: Where n≤3, m=7 or 8.
3. The high-strength and high-toughness silane-modified sealant according to claim 1, characterized in that: The plasticizer is one of polyether polyol and diisononyl phthalate; the anti-ultraviolet aging agent is one or both of UV329 and light stabilizer 770; and the antioxidant is one of 1010 and 1076.
4. The high-strength and high-toughness silane-modified sealant according to claim 1, characterized in that: The dewatering agent is vinyl trimethoxysilane; the coupling agent is one or two or more of KH550, KH560, KH570 and KH792; and the catalyst is a chelated tin catalyst.
5. A method for preparing a high-strength and high-toughness silane-modified sealant according to any one of claims 1 to 4, characterized in that: The steps include: In a reaction kettle, add the silane modified resin, nano calcium carbonate, and surface treatment agent, mix well, heat to 60-80°C for reaction for 1-2h, then heat to 110-120°C for reaction for 1-2h, then add plasticizer, UV aging agent, and antioxidant and mix well, stir for 1-2h at a vacuum of -0.1~-0.06MPa and a temperature of 110-120°C, then cool to below 50°C, add reinforcing plasticizer, dehydrating agent, coupling agent, and catalyst, mix well in vacuum, release pressure with nitrogen, and seal the discharged material for storage.
Citation Information
Patent Citations
Sealant composition, silane modified polyether sealant and preparation method of sealant
CN113249075A
Single-component silane-modified polyether sealant for prefabricated buildings and preparation method therefor
WO2021232819A1
Cited By
Weather-resistant modified silane sealant and preparation method thereof
CN122278416A